2021
DOI: 10.1038/s41598-020-80472-1
|View full text |Cite
|
Sign up to set email alerts
|

The loading effect of Pt clusters on Pt/graphene nano sheets catalysts

Abstract: In this paper, we report about chemically interaction between Pt Subnano-Clusters on Graphene Nano Sheets (GNS). The aim of this research is to clarify the size effect of Pt clusters on Pt 1–7 wt.%/GNS. This research is an experimental laboratory research. GNS was synthesized by using modified Hummer’s method and 1–7 wt.% Pt/GNS were prepared with impregnation method. Then, they were analyzed with TG/DTA, XRD, TEM and XPS, respectively. The results show that Pt clusters are well deposited on GNS (TG/DTA and TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 46 publications
(37 reference statements)
0
10
0
1
Order By: Relevance
“…X-ray photoelectron spectroscopy (XPS) measurements in Figure g showed a difference in binding energy for reduced Pt on graphene, with Pt 4f 5/2 at 74.6 eV and Pt 4f 7/2 at 71.3 eV when compared to reduced Pt on Si samples, with Pt 4f 5/2 at 74.3 eV and Pt 4f 7/2 at 70.9 eV. The 0.3 to 0.4 eV shift in binding energy has been attributed to enhanced interaction in the Pt–C due to the C π*–Pt d hybridization only observable in low loadings of Pt nanoparticles. , This Pt–C interaction, detectable only after reduction, should allow for improved modulation of electron density of the Pt clusters. These observations, as well as height profiles obtained from the scanning tunneling microscopy (STM) image in Figures h and S8, are consistent with a thin discontinuous layer of Pt nanoclusters 2–4 nm in height on a continuous layer of graphene.…”
Section: Resultsmentioning
confidence: 99%
“…X-ray photoelectron spectroscopy (XPS) measurements in Figure g showed a difference in binding energy for reduced Pt on graphene, with Pt 4f 5/2 at 74.6 eV and Pt 4f 7/2 at 71.3 eV when compared to reduced Pt on Si samples, with Pt 4f 5/2 at 74.3 eV and Pt 4f 7/2 at 70.9 eV. The 0.3 to 0.4 eV shift in binding energy has been attributed to enhanced interaction in the Pt–C due to the C π*–Pt d hybridization only observable in low loadings of Pt nanoparticles. , This Pt–C interaction, detectable only after reduction, should allow for improved modulation of electron density of the Pt clusters. These observations, as well as height profiles obtained from the scanning tunneling microscopy (STM) image in Figures h and S8, are consistent with a thin discontinuous layer of Pt nanoclusters 2–4 nm in height on a continuous layer of graphene.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of characteristic Pt peaks in the sample Pt/Li-GR is probably due to the low Pt mass loading in the generated Pt/Li-GR sample. In the literature, F. Hutagalung et al reported that the Pt XRD peaks are not visible for a Pt supported carbon with a metal loading below 1 wt% [44]. Besides, Raman spectroscopy is a convenient method for investigating insertion materials process [45].…”
Section: Resultsmentioning
confidence: 99%
“…X-ray photoelectron spectroscopy (XPS) results prove that Pt metal is the main component of the catalyst (Figure S3, Supporting Information). [37] 2.2. Carrier Transport and Light Management on Quartz Glass/Perovskite/Silicon Photoelectrode A schematic highlighting the structure and energy band diagram of quartz glass-protected perovskite/silicon-based photocathode is displayed in Figure 2a.…”
Section: Resultsmentioning
confidence: 99%
“…X‐ray photoelectron spectroscopy (XPS) results prove that Pt metal is the main component of the catalyst (Figure S3, Supporting Information). [ 37 ]…”
Section: Resultsmentioning
confidence: 99%